Estudio de viabilidad socio ambiental de una planta de clasificación de residuos sólidos urbanos para el cantón Riobamba - Checa Altamirano, Belén Estefanía (2020)
An urban reliable waste classification plant serves to separate recoverable materials and then used them. The purpose of the study is to present socio-environmental indicators to determine its viability in the Riobamba city. The research methodology was based on a compilation of information from primary and secondary sources. The data was analyzed using the PER system (Pressure-State-Response). To determine the socio-environmental impacts was carried out, using the Leopold Matrix. In the compilation of information from primary and secondary sources, the solid waste management of the Riobamba is described, revealing socio-environmental problems such as waste generation, the situation of the base miners, points of infection of the city, differentiated collection in rural areas and the lack of treatment before final disposal. These pressures were analyzed in the PER system, where the social response is environmental regulations -Concluding that the current answer is not sufficient or efficient to respond to the pressures and the best response is the creation of a classification plant. The production of the plant does not generate negative impacts of great magnitude and importance, on the contrary, it creates positive effects such as: job creation, quality of life, profitability, economic development, health, education, leachate infiltration decreases, air quality improves, reduces GHG emissions and bad odors. The study proved to be environmentally and socially viable.